Green’s relations on the deformed transformation semigroups - Tsyaputa, G.Y. (Algebra and Discrete Mathematics, 2004)
Green’s relations on the deformed finite inverse symmetric semigroup ISn and the deformed finite symmetric semigroup Tn are described.